Effect of tele-exercise versus combination of tele-exercise with tele-counselling on obese office employee’s weight loss - Mury Kuswari; Rimbawan Rimbawan; Hardinsyah Hardinsyah; Mira Dewi; Nazhif Gifari (UHAMKA PRESS, 2021)
Obesity is one of five death risks globally. This is worsened by the increasing sedentary nature of work, where adults spend most of their time. The ongoing COVID-19 pandemic causes many employees to work from home. Online exercise in home or tele-exercise may potentially manage this. The purpose of this study was to analyze the effectiveness of tele-exercise on decreasing body weight of obese employee, or if it must be combined with nutrition tele-counseling. The design of this study is Pre-Post-Test Quasi-Experimental. This study was conducted on obese office employee in Jakarta with two intervention groups, one who receive tele-exercise intervention and the other who receive tele-exercise and nutrition tele-counseling. Subjects were divided into tele-exercise (n=25) and tele-exercise and nutrition tele-counseling (n=38). Subjects received tele-exercise 30 minutes per session, three sessions per week for six weeks. Tele-counseling was done by WhatsApp application every day, consisting of balanced nutrition education and calorie restriction for weight loss. Paired t-test was done on subject’s body weight before and after intervention. The group who received tele-exercise and tele-counseling experienced weight loss significantly with average bodyweight from 77.36±11.83 kg to 75.49±11.58 kg (Δ=-1.87 kg, p<0.05), while the same didn’t happen on another group (Δ=0.36, p>0.05). This research showed that tele-exercise is not very effective on decreasing obese office employee’s body weight, but must be combined with nutrition tele-exercise to achieve significant weight loss.